Media Massa, Tutorial Aksi Kejahatan - Untung Sumarwan (Universitas Budi Luhur, 2017)
The basic principle of media coverage, now almost no longer a commander of the community, because the insistence of various economic interests and business. Especially in the world of television, which is more visible to highlight its role as a capital-intensive industry and profitable pursuit. Some assume that news and television shows are always the truths that are worth imitating. Unfortunately, it is not only about the goodness that is imitated but also the 'recording' of the bad image and the evil of an impression. Media impressions can inspire. Not only the positive one but also the bad. The good and the bad are comparable and have the right to both be watched and imitate. The impact of imitation is what gives rise to different risks, can be good and evil. A media impression can be a good and inspiring mentor of good deeds. Conversely often also become a tutor in a crime. One function of the media is to educate, therefore through the news that is not only a matter of fact but also think of the impact that will be generated is the best method of education by the media as an effort to reduce crime.